2019
DOI: 10.12681/jhvms.19617
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in the CSN2, CSN3, LGB and LALBA genes with milk production traits in Holstein cows raised in Turkey

Abstract: A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) test was performed on DNA samples extracted from blood samples of 189 Holstein Friesian cows to detect genotypic distribution of polymorphic markers in the bovine beta-casein (CSN2), kappa-casein (CSN3), beta-lactoglobulin (LGB) and alfa-lactalbumin (LALBA) genes responsible for milk production traits. Statistical analysis was carried out using least square methods of the general linear model (GLM) procedure. CSN2 locus was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
(65 reference statements)
1
15
0
Order By: Relevance
“…Our results showed that Maghrebi camels with A/A genotypes had a higher protein percentage with higher acidity. Previous studies have reported a significant association of CSN2 gene polymorphisms with higher protein and casein content in cattle (Nilsen et al, 2009;Bugeac et al, 2015;Bhat et al, 2017;Viale et al, 2017;Soyudal et al, 2018). The association between the CSN2 gene polymorphisms and milk protein percentage of our study might be attributed to the modification of the mRNA stability and transcription rates (Szymanowska et al, 2004;Kuss et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our results showed that Maghrebi camels with A/A genotypes had a higher protein percentage with higher acidity. Previous studies have reported a significant association of CSN2 gene polymorphisms with higher protein and casein content in cattle (Nilsen et al, 2009;Bugeac et al, 2015;Bhat et al, 2017;Viale et al, 2017;Soyudal et al, 2018). The association between the CSN2 gene polymorphisms and milk protein percentage of our study might be attributed to the modification of the mRNA stability and transcription rates (Szymanowska et al, 2004;Kuss et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies have reported a significant association of CSN2 gene polymorphisms with higher protein and casein content in cattle (Nilsen et al, 2009;Bugeac et al, 2015;Bhat et al, 2017;Viale et al, 2017;Soyudal et al, 2018). The association between the CSN2 gene polymorphisms and milk protein percentage of our study might be attributed to the modification of the mRNA stability and transcription rates (Szymanowska et al, 2004;Kuss et al, 2005). Moreover, the 2126 A/G SNP of CSN2 gene is located three nucleotides downstream of the TATA box and that might modify the binding affinity of RNA polymerase and change the gene expression (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The considerable genetic variation that exists within the LALBA gene across species also offers potential insights to its core functional elements. At the nucleotide level, there is a multitude of SNP within both the 5'UTR and coding regions of the LALBA gene, although few have been analyzed for their association with milk yield or composition [165,[169][170][171][172][173][174][175][176][177]. At one extreme, a single SNP 15 bp away from the LALBA TSS in Holstein cows was associated with higher lactose content and milk yield, but lower fat and protein content, and was proposed to account for a 30-fold greater expression of LALBA in explants from Holstein versus Angus cows [171,178,179].…”
Section: Genomic Variation and The Regulation Of Lalba Functionmentioning
confidence: 99%
“…Such selection is often used to increase the frequency of preferable alleles in the population in order to gain economic benefits. Producers may also incorporate genomic selection into their breeding programmes in order to reduce generation intervals and improve the overall performance of their herds [ 6 ].…”
Section: Introductionmentioning
confidence: 99%